The future of the Protestant Church: Estimates for Austria and for the Provinces of Burgenland, Carinthia and Vienna - Anne Goujon; Claudia Reiter (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2020)
Secularization and migration have substantially affected the place of the Protestant Church in the Austrian society in the last decades. The number of members has been shrinking markedly from 447 thousand members in 1971 to 278 thousand in 2018. The trend is visible across all provinces, although the magnitude is stronger in Vienna where both disaffiliation and international migration are stronger: In the capital city, the Protestant population diminished from 126 thousand to 47 thousand over the 1971-2018 period. Using population projections of membership to the Protestant Church, we look at the potential future of affiliation to the Protestant Church in Austria, and in three provinces: Burgenland, Carinthia, and Vienna from 2018 to 2048, considering different paths of fertility and disaffiliation. We also look at the impact of different scenarios regarding the composition of international migration flows on affiliation to the Protestant Church. Our findings suggest that in the absence of compensatory flows, the Protestant Church will keep shrinking unless it manages to stop disaffiliation. The projections also show that migrants, especially within mobile Europe, are a potential source of members that is at present not properly contributing to membership in Austria. According to the TREND EUROPE scenario, which is - seen from today - the most likely scenario with a continuation of declining entries and increased exits, the Protestant population in Austria would still decline from 283 thousand in 2018 to 144 thousand in 2048 (-49%). At the level of the three provinces, the decline would be faster in Vienna (-42%, from 47 to 27 thousand) than in Burgenland (-26%, from 32 to 24 thousand) and Carinthia (-37%, from 48 to 30 thousand). According to this scenario, by 2048 the Protestant population would correspond to 1.5% of the total population of Austria(1.3% in Vienna, 7.3% in Burgenland and 5.4% in Carinthia). Other scenarios reflect the potential impact of different religious composition of future migrant flows, as well as changing disaffiliation patterns. Only under the LIFT scenario, which assumes a reduction in exits by 50% and more migrants enrolling to the Protestant Church, we see an end of the haemorrhage and even an increase in the number of Protestants in Vienna. – – In Anlehnung an den Bericht von Goujon, Jurasszovich und Potančoková (2017), der die Bevölkerung von Wien und Österreich nach Religionszugehörigkeit für den Zeitraum 2001-2016 schätzte, sowie an ein früheres Projekt von Fliegenschnee, Goujon und Lutz (2004), das sich mit der Zukunft der evangelischen Kirche bis 2031 beschäftigte, soll dieses Projekt anhand der neuesten Daten für ganz Österreich und die drei Bundesländer Burgenland, Kärnten und Wien aktualisiert werden. Ziel der vorliegenden Studie soll es sein, die Frage nach den möglichen Auswirkungen der Demographie (insbesondere Fertilität und Migration) und dem Trend zum Religionsaustritt auf die künftigen Mitgliederzahlen der evangelischen Kirche zu beantworten.
Keywords: 300; Protestant Church; Austria; Austrian provinces; membership projection; secularization; migration